Patterns of revascularization in stable ischemic heart disease in the pre-ISCHEMIA era. (25th November 2020) - Albuquerque, F; Brizido, C; Madeira, S; Teles, R; Raposo, L; Gabriel, H; Leal, S; Goncalves, M; Brito, J; Goncalves, P; Almeida, M; Mendes, M
Abstract: Introduction: New evidence on the role of myocardial revascularization in stable ischemic heart disease (SIHD), recently presented, showed that revascularization guided by the presence of moderate-to severe ischemia relieves angina more effectively than optimal medical therapy (OMT), without a significant benefit in hard clinical endpoints. Aim: To assess the representativeness of the ISCHEMIA trial in a real-world population and compare management strategies between patients who fulfill the eligibility criteria of the trial (Group 1, G1) and those who do not (Group 2, G2). Methods and population: Single centre retrospective analysis including all consecutive patients referred to coronary angiography (CA) for SIHD from January 2018 to December 2019. Patients were stratified in two groups (G1 and G2) according to the ISCHEMIA trial inclusion and exclusion criteria. G1 was compared with G2 and with a subset of G2 with obstructive coronary artery disease (CAD), defined as ≥70% luminal stenosis in at least one coronary artery or >50% for the left main. Results: A total of 1020 patients underwent CA, of whom only 124 (12.2%) would have been eligible for the ISCHEMIA trial (G1). Overall, there were no significant differences in baseline characteristics between the two groups. G1 patients had more extensive and severe disease, presenting more frequently with proximal left anterior descending (LAD) involvement (26.6% vs 10.4%; p<0.001), two vessel disease without proximal LAD stenosis (23.4% vs 10.3%; p<0.001) and three vessel disease (18.5% vs 5.9%; p<0.001). These patients had higher rates of revascularization, both CABG (25.8% vs 10.8%, p<0.001) and PCI (56.5% vs 39.5%, p<0.001). However, when comparing G1 with the subset of G2 patients with obstructive CAD, G1 patients had higher rates of CABG (26.8% vs 17.8%, p=0.034) but there were no differences on the rates of PCI (58.0% vs 56.9%, p=0.916). Conclusions: Patients included in the ISCHEMIA trial are underrepresented in a real-world population of SIHD patients referred to coronary angiography. PCI rates were similar among patients with at least one significant coronary artery stenosis, regardless of previous evidence or severity of ischemia. Our findings underline the need for further refinement in criteria for revascularization in SIHD. Funding Acknowledgement: Type of funding source: None